Turkey's security understanding and its relation with the European Union in the 1990s. (3rd July 2017) - Ayaz Avan, Esengül
ABSTRACT: While the end of the Cold War challenged the classical understanding of national security in Europe, Turkey continued to follow a national security-centered and confrontational foreign policy during the 1990s due to its internal and external security problems. Although this created important differences in security understandings and policies between Turkey and the European Union (EU), Turkey continued to seek EU membership during the 1990s. The goal of this paper is to answer why Turkey was willing to join the EU in the 1990s despite its difficulty in balancing its relations with the EU with its security problems. The main conclusion of the paper is that Turkey's eagerness to join the EU during the 1990s can be explained by both the perception of EU membership as the most appropriate and desired policy for Turkey and Turkey's eagerness to ensure its political and security objectives.